The chemical element : chemistry's contribution to our global future - Garcia-Martinez, Javier; Serrano-Torregrosa, Elena (Weinheim, Germany : Wiley-VCH, 2011)
"United Nations has declared 2011 the International Year of Chemistry, to celebrate the achievements of chemistry and its contributions to the well-being of humankind. In this book, prominent scientists highlight the major advances in the fight against the largest problems faced by humanity from the point of view of chemistry, showing how science is essential to ensuring our long-term survival. Following the UN Millennium Development Goals, the authors examine the nine most critical areas, including energy, climate, food, water, poverty, education and health. All of them are opinion leaders in their fields, or high-ranking decision makers in national and international institutions. This book provides an intellectual basis for the future development of chemistry, it is aimed at a wide readership including students, professionals, engineers, scientists, environmentalists and anyone interested in a more sustainable future"--P. [4] of cover.
Foreword / Nicole Moreau and Julia Hasler -- Chemistry for development / Stephen A. Matlin and Berhanu M. Abegaz -- The role of chemistry on addressing hunger and food security / Jessica Fanzo, Roseline Remans and Pedro Sanchez -- Poverty / Mari-Carmen Gomez-Cabrera, Cecilia Martinez-Costa, Juan Sastre -- The human element : chemistry education's contribution to our global future / Peter Mahaffy -- Health / Rene Roy -- Green chemistry / Pietro Tundo, Fabio Aricoa, Con Robert McElroy -- Water : foundation for a sustainable future / Maya A. Trotz, James R. Mihelcic, Omatoyo K. Dalrymple, Arlin Briley, Ken D. Thomas, and Joniqua A. Howard -- Facing the energy challenges through chemistry in a changing world / Gabriele Centi and Siglinda Perathoner -- Ozone layer depletion / Glenn Carver -- Epilogue / Jeffrey Sachs.
Includes bibliographical references and index.
Keywords: Environmental chemistry; Sustainable development